AN ANALYSIS OF STUDENTS’ SATISFACTION AT LOCAL STREET COFFEE SHOP IN PENANG - Nurul’Aishah Zakaria; Noraini Jaafar; Nurul Istiqomah Mohamad Fuad; Syuhirdy Mat Noor (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Street coffee shops are small, informal establishments often found in busy urban areas, offering a limited menu of coffee, tea, and light snacks. Known for their convenience, these shops cater to people on the move, commonly located in pedestrian-friendly zones or near public transport hubs. Customer satisfaction plays a crucial role in driving repeat visits and word-of-mouth referrals, making it essential for owners and managers to understand customer preferences and improve service. This study investigates factors influencing customer satisfaction at local street coffee shops, focusing on price, quality, and location. Additionally, the study considers the impact of competition among coffee shops and evolving market trends on customer satisfaction, emphasizing the importance of staying competitive in a dynamic environment. Demographic factors, such as age, gender, and income, are also analyzed to explore their influence on consumer preferences and satisfaction levels. Using simple random sampling, data was collected from 390 respondents via an online questionnaire. The results reveal that price, quality, and location significantly impact customer satisfaction in this setting. Based on these findings, the study offers recommendations for coffee shop managers and outlines suggestions for future research.